Clinical Significance of the HHLA2 Protein in Hepatocellular Carcinoma and the Tumor Microenvironment [Corrigendum] - Luo M; Lin Y; Liang R; Li Y; Ge L (Dove Medical Press, 2021)
Luo M, Lin Y, Liang R, Li Y, Ge L. J Inflamm Res. 2021;14:4217–4228. Page 4222, Correlation Between Tumor Microenvironment and Prognosis in HCC section, the text “Based on Teng et al,29 we defined four types of tumor microenvironment: type I (“adaptive immune resistance”, HHLA2 - high TILs +), which lacked HHLA2 and show intermediate or high TIL density, was observed in 77 of the 202 HCC tissues (38.1%); type II (“immunologic ignorance”, HHLA2 - low TILs -), which lacked HHLA2 and showed low TIL density, was observed in 10 cases (5.0%); type III (“intrinsic induction”, HHLA2 - high TILs -), which lacked HHLA2 and showed intermediate or high TIL density, was observed in 26 cases (12.9%); and type IV (“tolerance”, HHLA2 – low TILs +), which lacked HHLA2 and low TIL density, was observed in 89 cases (44.0%)” should read “Based on Teng et al,29 we defined four types of tumor microenvironment: type I (“adaptive immune resistance”, HHLA2 - high TILs +), which expressed high HHLA2 and showed intermediate or high TIL density, was observed in 77 of the 202 HCC tissues (38.1%); type II (“immunologic ignorance”, HHLA2 - low TILs -), which lacked HHLA2 and showed low TIL density, was observed in 10 cases (5.0%); type III (“intrinsic induction”, HHLA2 - high TILs -), which expressed high HHLA2 and showed low TIL density, was observed in 26 cases (12.9%); and type IV (“tolerance”, HHLA2 - low TILs +), which lacked HHLA2 and showed intermediate or high TIL density, was observed in 89 cases (44.0%)”. The authors apologize for this error. Read the original article